Peningkatan Pemahaman Dasar Komputer dan Microsoft Word Melalui Program Kelas Teknologi di SDI Al-Barokah - Rodhiah Filkhair; prayuda, kurnia sandi; M.Jihad Hendrawan; Muhaffivin Maedani; Elina Putri (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The Technology Class program is part of the KKN activities aimed at enhancing the understanding of elementary students at SDI Al-Barokah Kalijaga Tengah regarding basic computer technology. This study employed a quasi-experimental design with a descriptive quantitative approach to measure the program's effectiveness. The program was conducted every Saturday for two month and involved 90 participants from grades 4, 5, and 6. The topics covered included an introduction to computer and laptop devices, an explanation of their components and functions, and the use of Microsoft Word applications. The teaching method combined theoretical presentations and hands-on practice using computers. Evaluation results indicated an increase in the students' average scores from The average score increased from 60 in the pre-test to 85 in the post-test,reflecting a 25-point improvement. A total of 76 students (84.4%) successfully completed the practical tasks of typing. These findings demonstrate that the Technology Class program effectively equips students with essential technological skills to support their learning in the digital era